PENGARUH GAYA KEPEMIMPINAN KEPALA MADRASAH DAN MOTIVASI KERJA TERHADAP KINERJA GURU MADRASAH ALIYAH SWASTA SEKECAMATAN TEBET JAKARTA SELATAN - Betti Nuraini; Sari Nurlita (Jurnal Media Ekonomi (JURMEK), 2019)
The purpose of this study was to determine the influence of madrasa head leadership style and work motivation on the performance of private madrasa aliyah teachers in Tebet Subdistrict, South Jakarta. This research was conducted by the method of data collection by distributing questionnaires to 54 madrasa aliyah teachers. The results showed the relationship between the leadership style of the madrasa head (X1) and work motivation (X2) on teacher performance (Y) carried out simultaneously showed a relationship of 0.973 and had an influence of 97.3%. In the T-test results (partially) madrasa head style leadership variables (X1) obtained a tcount of 43.012 while a ttable of 2.008. Because tcount> ttable so that H0 is rejected and H1 is accepted which means partially X1 affects Y. Work motivation variable (X2) is obtained tcount of 2.310 while the ttable value of 2.008. Because tcount> ttable so that H0 is rejected and H1 is accepted which means partially X2 affects Y. Test results F (simultaneously) obtained Fcount of 926,194. At a significance level of 5% Ftable = 3.18 was obtained. Fcount> Ftable, then H0 is rejected and H1 is accepted so that it can be said that there is an effect of X1 and X2 together on Y. Madrasa head leadership style and work motivation on Madrasa aliyah teacher performance has a higher influence if the madrasa head leadership style and work motivation is carried out simultaneously.